STUDENTS’ PERCEPTION TOWARD THE USE OF YOUTUBE IN LEARNING VOCABULARY - Alfin Dwi Cahyono (Graduate Program, University of Islam Malang, 2021)
Abstract YouTube is easy for students to access via mobile phones or laptops. They can lookout videos in the schoolroom or in the schoolroom anytime, anyplace which builds them also actuated and keen to acquire. Since the YouTube site is free, both students and teachers can easily lookout and upload videos. Schoolteachers from complete the world birth created their have watercourses on YouTube and regularly upload severals dissimilar academic videos that pupils get utile. Covid-19 has been declared as a global pandemic by WHO. It affects all aspects of humans’ life, including their education. Teaching and learning processes during the pandemic of Covid-19 are done online. However, many Indonesian teachers have not used this teaching media and learned is its benefits yet. Therefore, this research was used to investigate students' views on using YouTube to learn English. This research adopts survey method. In addition, interviews will be conducted after this survey to obtain more in-depth data. The participation of survey data and interview data may make the survey results more reliable relative to the subject under study. The study involved forty-four students as study participants to answer the questionnaire. In addition, this study also tracked the results of the questionnaire by interviewing 3 of 44 participants. In order to collect data, the questionnaire was distributed using Google format media (with multiple choices) and Whatshapp media (recorder) to collect interview data. The survey results show that students have a positive view of YouTube. Most participants agree that they like youtube because it can help them learn English. Another positive effect is that students’ vocabulary has been improved. Therefore, the research results show that YouTube can be used as an alternative teaching medium to improve students' English learning level, especially vocabulary learning.